Naming the unnameable. The debate concerning the concept of political religion to define the totalitarisms (Estudios Sociales, 2019)
This paper intends to present an episode in the historical development of the concept of political religion as an interpretive tool of totalitarianisms, the period in which the concept begins to be questioned by recognized intellectuals. Debate around the legitimacy of the concept that should be understood as a chapter of two of the fundamental disputes of modernity, the quarrel about the meaning of secularization and about the status of political science. Chapter that has been ignored by the historians who have generated the present rebirth of the concept. Through this glass we will analyze the main arguments of the thinkers who have participated in this debate: Aron, Arendt, Kelsen y Voegelin.
Keywords: Political religion; Totalitarism; Secularism; Political Science